Remoção dos corantes alimentícios vermelho 40 e amarelo tartrazina utilizando o pó da folha da castanhola - COSTA, Thaísa Serra da (2023)
Incorrect disposal of dyes is a serious problem, as it is one of the main causes of industrial effluent pollution. Therefore, adsorption emerges as a viable alternative to treat such effluents. In the present study, the residue of the Castanet Leaf (CL) as an alternative biosorbent in the removal of food dyes Vermelho 40 (V40) and Amarelo Tartrazine (TA) in aqueous solutions was investigated. The biosorbent was characterized by infrared spectroscopy (FTIR), scanning electron microscopy (SCAN) and zero load point (pHpcz). The influence of pH, contact time, temperature and concentration were evaluated in batch system. The biosorbent showed maximum adsorption at pH 1,0 and equilibrium time of 360 minutes for both dyes. The kinetic model of pseudo-second order and the langmuir isothermal model were the ones that best fit the evaluation of adsorption of dyes. The maximum adsorption capacity determined for HR was 7,37 mg g-1 and 6,38 mg g-1 for dyes V40 and TA, respectively. The analysis of the thermodynamic study ΔGº, ΔHº and ΔSº, showed that the adsorption process for the dyes analyzed on CL was favorable and spontaneous, suggesting that phissortion occurs together with chemortion.